Fatalism, faith and fear: A case study of self‐care practice among adults with Type 2 diabetes in urban Malaysia - Saidi, Sanisah; Milnes, Linda; Griffiths, Jane (Wiley, 2018)
Aims and objectives: To explore self‐care and self‐care support in patients with Type 2 diabetes in urban Malaysia. Background: The prevalence of Type 2 diabetes in Malaysia and associated long‐ term and life‐changing complications is increasing. With effective self‐care and self‐ care support, severe complications of the condition can be avoided or reduced. Prior to this study, no evidence existed about Malaysian patients’ management of the condition or support for self‐care from the healthcare system. Design: A single embedded qualitative case study. Methods: Semistructured interviews with 18 patients with Type 2 diabetes aged 28–69 years, healthcare professionals (n = 19), observations (n = 13) of clinic appointments from two urban settings in Malaysia and a documentary analysis. Recordings were transcribed verbatim, field notes were made during observations and the data analysed and synthesised within and across case using Framework analysis. Findings: Three main themes explained self‐care and self‐care support in Malaysia: fatalism, faith and fear. Patients were fatalistic about developing diabetes—they perceived it as inevitable because it is so common in Malaysia. However, faith in God, coupled with fear of the consequences of diabetes, motivated them to engage in self‐care practices. The fear was largely induced by diabetes healthcare professionals working in overcrowded clinics, and stretched thinly across the service, who used a direct and uncompromising approach to instil the importance of self‐care to avoid severe long‐term complications. Conclusion: This study provided important insight on how people in Malaysia developed diabetes, their responses to the disease and the approach of healthcare professionals in supporting them to engage with self‐care. Relevance to clinical practice: Any future development of self‐care programmes in Malaysia needs to recognise the factors that motivate patients to self‐care and include components that build self‐efficacy